STEAM HEATING SUPPLY SYSTEM EQUIPMENT. - Mahsitaliev Barkhayotjon Iftikhorjon ugli,; Salimov Abdulkadir Kabirjon ugli, (Ustozlar uchun, 2025)
This article analyzes the main equipment used in steam heating supply systems and their functions. Steam heating systems are an effective means of transferring heat energy in industrial and residential buildings. Various devices are used in these systems to control, manage and protect pressure, temperature, steam consumption and water level. In particular, manometers, thermometers, pressure regulators, condensate drains (condensate pipes), air vent valves and other control and measuring devices are widely used. The article covers the principle of operation, structure, arrangement and importance of these devices in steam systems. Special attention is also paid to high-efficiency devices selected based on modern energy saving requirements.